تقييم أداء بروتوكولي التوجيه GPSR وAODV عند التقاطعات في شبكات العربات المتنقلة - بشرى معلا; بسام حسن (Tishreen University, 2017)
تتألف شبكات العربات المتنقلة من مجموعة من العقد تشكل شبكة لاسلكية، لكن عقد هذه الشبكة هي عربات ذات تجهيزات خاصة تجعلها قادرة على الاتصال فيما بينها. تواجه بروتوكولات التوجيه في VANET تحديات كبيرة تتمثل بالتغير الديناميكي لطوبولوجيا الشبكة، كذلك كسر الوصلة والكثافة المنخفضة للعربات. يساعد بروتوكول التوجيه المناسب والفعال بضمان وصول الرسائل إلى الوجهة المطلوبة وتحقيق الهدف من التطبيق. نقدم فـي هذا الـبحث تحلــيلاً لأداء اثنين من أهـــم بروتــوكولات التوجـيه المــستخدمـة في هـذه الـشبكـات وهي البـروتوكـولين AODV وGPSR. يعتمد هذا التحليل على بارامترات مختلفة مثل التأخير نهاية إلى نهاية ومعدل فقدان الرزم بهدف الوصول إلى أفضل بروتوكول يمكن استخدامه في حال كانت الشبكة منخفضة الكثافة عند التقاطعات. لتحقيق هذا الغرض استخدمنا المحاكي OPNET_17.5، واعتماداً على نتائج المحاكاة التي حصلنا عليها وبالتحليل والمقارنة بين هذين البروتوكولين عند كثافة عقد منخفضة مختلفة وجدنا أن البروتوكول GPSR ذو أداء أفضل من حيث التأخير نهاية إلى نهاية ومعدل فقدان الرزم كبارامترين أساسيين مستخدمين لتقييم الأداء، وهو البروتوكول الأفضل من أجل سيناريو شبكة VANET ذات الكثافة المنخفضة للعربات عند منطقة التقاطعات. Abstract: A Vehicular Ad-hoc Network (VANET) is a collection of nodes forming a wireless network, but the nodes of this network are vehicles with special equipment that enable them to communicate with each other. VANET protocols have to face high challenges due to dynamically changing topologies, link breakage and low vehicular density. A suitable and effective routing protocol helps to ensure that messages are reached to their destinations and achieve the desired aim of the application. In this research, we present an analysis of the performance of two major routing protocols used in these networks, which are AODV (Ad hoc On-Demand Distance Vector) and GPSR (Greedy Perimeter Stateless Routing). This analysis is based on various parameters such as end-to-end delay and average dropped packets, in order to find the best protocol which can be used in the network with low density at the junctions. To achieve this purpose, we used a simulator OPNET_17.5. Depending on the simulation results, we have obtained and the analysis and comparison of two protocols at different low density contract. We found that GPSR protocol has better performance end-to-end delay and average dropped packets are used as the performance metrics, and is better for VANET under the low vehicular density simulation scenario at junctions.